PENGARUH STRATEGI GREEN TOURISM DIFFERENTIATION TERHADAP KEPUASAN DAN MINAT KUNJUNG ULANG WISATAWAN HUTAN MANGROVE DI KABUPATEN KEBUMEN - Pratama, Marynta Putri; Wibawanto, Sigit (P4M STIE Putra Bangsa, 2019)
Differentiation of green tourism towards satisfaction and interest in tourists visiting mangroves in Kebumen District. In 2017 Kebumen Regency is developing the natural tourism sector, one of which is the tourism of mangrove forests which is designated as ecotourism. Based on the number of visitor reports, which is known to occur in a significant number of visitors. Some visitors are visitors who visit again. For this reason, it is necessary to examine the marketing strategy development model that is able to assess factors that can increase competitiveness and tourist visits, as a basis for developing natural tourism in other natural attractions. The research methods used are quantitative descriptive surveys. The population in this study is mangrove tourists who have visited more than twice in one year. The sampling technique in this study uses convenience sampling. The statistical test tool used is path analysis with the help of the SPSS version 22 program.Keywords: Green Differentiation Tourism, Satisfaction, Revisiting Interests.